Compare with different vegetable oils on the quality of the Nemipterus virgatus surimi gel. Issue 9 (2nd June 2022) - Song, Chunyong; Lin, Yufeng; Hong, Pengzhi; Liu, Huanming; Zhou, Chunxia
Abstract: To enhance the quality and flavor of surimi‐based products, we investigated the effects of vegetable oils (peanut, soybean, corn, coconut, olive, and safflower seed oils) on the texture, water‐holding capacity (WHC), microstructure, and flavor of the Nemipterus virgatus surimi gel. The results showed that 6 kinds of vegetable oils could improve the whiteness and flavor of gels. However, peanut, olive, and coconut oils enriching oleic acid or lauric acid were easy to accumulate with an average diameter of more than 0.15 μm. Thus, the gel with the oil showed a loose network structures with large cavities, and the texture was deteriorated, accompanied by decreased WHC ( p  < .05). Compared with other vegetable oils, soybean, corn and safflower seed oils enriching linoleic acid were emulsified with protein forming a stable interfacial protein film. The gel with the oil showed an increase in the WHC and bound water content. Furthermore, the oil droplets with an average diameter of less than 0.15 μm were evenly distributed in the gel matrix, and the gel exhibited dense network structures with small cavities and smooth surface. In general, soybean and safflower seed oils can be used as a potential additive to improve the quality and flavor of surimi‐based products. Abstract : Vegetable oils can improve the whiteness and flavor of surimi gel. Surimi gels with soybean, corn, or safflower seed oils have a denser gel 3D network structure than those with other vegetable oils. High‐quality of surimi‐based products can be produced by adding vegetable oils that rich in polyunsaturated fatty acids.